2008
DOI: 10.1007/s11430-008-0049-9
|View full text |Cite
|
Sign up to set email alerts
|

Observation and study on the whole process of cloud-to-ground lightning using narrowband radio interferometer

Abstract: A narrowband radio interferometer has been developed and used to locate the entire sources of VHF radiations from a negative cloud-to-ground (CG) lightning discharge which contains 19 strokes. This system uses five antennas to form an array consisting of short-and long-baselines along two orthogonal directions. The system error which comes from frequency conversion is reduced by phase detection through direct high frequency amplifying. An interactive graphic analysis procedure is used to remove the fringe ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

8
0

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 9 publications
(3 reference statements)
2
17
0
Order By: Relevance
“…The velocity of the preliminary breakdown was 5.2×10 4 m/s and that of the stepped-leader was 1.3×10 5 m/s, similar to the results by Shao et al [1][2][3]. The polarity of breakdown was mostly negative corresponding to the positive pulses in the waveform of electric field.…”
Section: Error Estimatesupporting
confidence: 87%
See 1 more Smart Citation
“…The velocity of the preliminary breakdown was 5.2×10 4 m/s and that of the stepped-leader was 1.3×10 5 m/s, similar to the results by Shao et al [1][2][3]. The polarity of breakdown was mostly negative corresponding to the positive pulses in the waveform of electric field.…”
Section: Error Estimatesupporting
confidence: 87%
“…People are more concentrated on the CG flash since CG flash is the cause of most lightning damage, injury, and death. Many meaningful results [1][2][3] based on the lightning locating technology and researches on the cloud-to-ground lightning mechanism have been obtained due to the application of low frequency CG lightning locating system and VHF interferometer system (2D). Recently, technology of lightning detecting has been greatly improved on the precision aspect.…”
mentioning
confidence: 99%
“…K-change is with relative small EFC in latter part of lightning. Shao et al [5] and Zhang et al [4] suggested that the M-component is a special K-change connected to a good conductive channel. Ogawa and Brook [7] suggested that the K-change can be seen as small RS in cloud.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…DATA AND CLASSIFICATION OF RPBS The data in this paper were recorded by VHF receiver (with bandwidth between 267-273MHz) and broadband electric field change (EFC) detector (with bandwidth between 0-10MHz, and time constant of 100us) in Binzhou of Shandong province , China, in the summer of 2007 [3,4]. Both VHF radiation and broadband EFC signals were recorded with 50ns time resolution using 20MHz digitizer and accurately phase locked to 1 pulse per second output of a GPS receiver.…”
Section: Introductionmentioning
confidence: 99%
“…A 3D lightning radiation source locating system (LLR for short), based on the TOA technique, was developed in 2004 and it has recorded considerable amounts of data, analyses of which have been published in many papers (Zhang et al, 2008Li et al, 2012Li et al, , 2013Wu et al, 2013;Fan et al, 2014). The LLR can obtain both the location of lightning radiation sources in distant thunderstorms and the spatiotemporal characteristics of the 3D lightning discharge channel with high accuracy.…”
mentioning
confidence: 99%